Implementation of a national school-based Human Papillomavirus (HPV) vaccine campaign in Fiji: knowledge, vaccine acceptability and information needs of parents - La Vincente, S. F. (BMC Public Health, 2015)
BACKGROUND: In 2008 Fiji implemented a nationwide Human Papillomavirus (HPV) vaccine campaign targeting all girls aged 9–12 years through the existing school-based immunisation program. Parents of vaccine-eligible girls were asked to provide written consent for vaccination. The purpose of this study was to describe parents’ knowledge, experiences and satisfaction with the campaign, the extent to which information needs for vaccine decision-making were met, and what factors were associated with vaccine consent. METHODS: Following vaccine introduction, a cross-sectional telephone survey was conducted with parents of vaccine-eligible girls from randomly selected schools, stratified by educational district. Factors related to vaccine consent were explored using Generalised Estimating Equations. RESULTS: There were 560 vaccine-eligible girls attending the participating 19 schools at the time of the campaign. Among these, 313 parents could be contacted, with 293 agreeing to participate (93.6 %). Almost 80 % of participants reported having consented to HPV vaccination (230/293, 78.5 %). Reported knowledge of cervical cancer and HPV prior to the campaign was very low. Most respondents reported that they were satisfied with their access to information to make an informed decision about HPV vaccination (196/293, 66.9 %). and this was very strongly associated with provision of consent. Despite their young age, the vaccine-eligible girls were often involved in the discussion and decision-making. Most consenting parents were satisfied with the campaign and their decision to vaccinate, with almost 90 % indicating they would consent to future HPV vaccination. However, negative media reports about the vaccine campaign created confusion and concern. Local health staff were cited as a trusted source of information to guide decision-making. Just over half of the participants who withheld consent cited vaccine safety fears as the primary reason (23/44, 52.3 %). CONCLUSION: This is the first reported experience of HPV introduction in a Pacific Island nation. In a challenging environment with limited community knowledge of HPV and cervical cancer, media controversy and a short lead-time for community education, Fiji has implemented an HPV vaccine campaign that was largely acceptable to the community and achieved a high level of participation. Community sensitisation and education is critical and should include a focus on the local health workforce and the vaccine target group.